MYASTHENIA GRAVIS AND CHRONIC INFLAMMATORY DEMYELINATING POLYNEUROPATHY IN A PATIENT WITH RECURRENT THYMOMA - Martić, Vesna V.; Fejzić, Esmer; Marić, Nebojsa (Srpski medicinski časopis Lekarske komore, 2023)
Myasthenia gravis (MG) and chronic inflammatory demyelinating polyneuropathy (CIDP) are autoimmune diseases aimed at different targets: in MG, it is the postsynaptic membrane of the skeletal musculature, while in CIDP, it is the peripheral nerves. Unlike MG, which can be observed in a significant percentage of patients with thymoma, the association of CIDP with MG and thymoma is rare.This is a report on a patient with a long-term history of myasthenia gravis with an unstable course, who was operated on several times because of the recurrence of thymoma. In the patient, after a long-term clinical remission lasting 16 years, and as part of the re-exacerbation of the thymoma, CIDP developed without signs of myasthenic weakness..
Keywords: Myasthenia gravis; CIDP; Thymoma